User survey of 3 ankle braces in soccer, volleyball, and running: Which brace fits best? - Janssen, K.; Van Den Berg, A.; Van Mechelen, W.; Verhagen, E. (Journal of Athletic Training, 2017)
Context: Recurrence rates for ankle sprains are high. Therefore, preventive measures such as ankle bracing during sports are recommended.